Cemetery Boys - Thomas, Aiden (New York : Swoon Reads, 2020)
Yadriel, a trans boy, summons the angry spirit of his high schools bad boy, and agrees to help him learn how he died, thereby proving himself a brujo, not a bruja, to his conservative family.
Publishers Weekly
Booklist
Kirkus Reviews
School Library Journal
12-19
7-12
Keywords: Transgender people -- Juvenile fiction; Witches -- Juvenile fiction; Magic -- Juvenile fiction; Spirits -- Juvenile fiction; Latin Americans -- Juvenile fiction; Family life -- Juvenile fiction; Transgender people -- Fiction; Witches -- Fiction; Magic -- Fiction; Spirits -- Fiction; Latin Americans -- Fiction; Family life -- Fiction